Linear models : an integrated approach - Sengupta, Debasis (Series on multivariate analysis ;, 2003)
Linear Models: An Integrated Approach aims to provide a clearand deep understanding of the general linear model using simplestatistical ideas. Elegant geometric arguments are also invoked asneeded and a review of vector spaces and matrices is provided to makethe treatment self-contained.